From rural microcenters to learning communities: an opportunity for dialogical transformation - Zapata, Viviana Alejandra (2019)
This paper presents a review of the state of the art of rural education, specifically microcenters from a learning communities’ perspective. The relationship and dissonances between both concepts will be established from a practical teaching point of view and its contextualization. The methodology included a review of the normative and scientific literature at the national and international level in order to understand and explain the problem in the Twentieth and Twenty-First Centuries. The approach used is the critical theory in education. It is concluded that rural microcenters have the potential to transform into a practical learning community, contributing to the improvement of qualitative and quantitative learning outcomes of students and mainly,